PENGARUH PENERAPAN DOKUMENTASI SISTEM, PERENCANAAN KERJA, PENGAWASAN KERJA, LINGKUNGAN KERJA, dan PELATIHAN KERJA TERHADAP KEPUASAN KERJA KARYAWANWASKITA KARYA SEMARANG - Ratih Dwi Hastari; Naili Farida; Hari Susanta Nugraha (Universitas Diponegoro, 2014)
This research aims to determine the effect of system documentation, job planning, supervision of work, work environment, and job training on employee job satisfaction. The type of this research is using explanatory research with 50 respondents drawn using non probability sampling techniques. The analysis method of this research is using multiple regression analysis. Using a Likert Scale as the measuerment scale. The analysis method using linear regression analysis and the significance test with SPSS 16.0. From the result of data analysis it can be concluded that in partial documentation system has a positive effect on job satisfaction of employees by 25,5%, the variable job planning has a positive effect on employee job satisfaction of 44,1%, variable work supervision has a positive effect on employee job satisfaction of 23,6%, a positive work environment variables impact on job satisfaction of employees is 38,9%, the variable job training has a positive effect on employee job satisfaction by 24%.